Mapping the landscape of spatial literacy research: Bibliometric analysis - Lai, Chan Kar; Mustafa, Mazlina Che; Mahat, Hanifah (International Journal of Publication and Social Studies, 2024)
The study aims to provide a comprehensive overview of spatial literacy research through a bibliometric analysis, focusing on its development, essential themes, key contributors, and collaboration patterns. Using statistical text-mining and citation link-based clustering techniques, 690 spatial literacy publications from the Scopus database were analyzed, with data extracted on February 18, 2024. The analysis revealed a steady increase in spatial literacy publications, peaking in 2009, and identified key peaks in cited papers in 1996, 2003 and 2012, with a subsequent decline post-2012. Document profiles primarily consisted of articles (60.14%) and sourced from journals (67.97%), with The Journal of Geography being the most active title. Notably, Newcombe, N.S., emerged as the most productive author, while the work of Bednarz and Kemp received the highest number of citations. ‘The Separability of Working Memory Resources for Spatial Thinking and Language Processing: An Individual Differences Approach’ by Shah and Miyake was identified as the most influential document, garnered a minimum of 100 citations per written document. Additionally, the United States stood out with both the largest number of publications and the highest citation impact in spatial literacy research. This bibliometric analysis provides valuable insight into the spatial literacy research landscape, guiding for future research directions and fostering collaborations in this field.